2016
DOI: 10.1016/j.tra.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Short-term planning and policy interventions to promote cycling in urban centers: Findings from a commute mode choice analysis in Barcelona, Spain

Abstract: a b s t r a c tBackground: Cycling for transportation has become an increasingly important component of strategies to address public health, climate change, and air quality concerns in urban centers. Within this context, planners and policy makers would benefit from an improved understanding of available interventions and their relative effectiveness for cycling promotion. We examined predictors of bicycle commuting that are relevant to planning and policy intervention, particularly those amenable to short-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 68 publications
8
57
2
Order By: Relevance
“…Residential density [30] • Parcel level density was positively related to the frequency of walking for transport and not related to the participation in walking for transport • Area level density was not related to the frequency of walking for transport and negatively related to the participation in walking for transport Land use mix [48] • Land use mix was positively related to walking for errands • Land use mix was not related to walking to work/school Street connectivity [64] • 500-m buffer: street connectivity was positively related to walking for transport • 1000-m buffer: street connectivity was not related to walking for transport Walkability [25] • Walkability was positively related to the participation in walking for transport • Walkability was not related to the duration of walking for transport [42] • Walkability was positively related to the frequency of walking for transport • Walkability was not related to the duration of walking for transport Bicycle lane [61] • Bicycle lane was not related to cycling for transport • Bicycle network connectivity was positively related to cycling for transport Table 9. Cont.…”
Section: Built Environment Factors Reference Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residential density [30] • Parcel level density was positively related to the frequency of walking for transport and not related to the participation in walking for transport • Area level density was not related to the frequency of walking for transport and negatively related to the participation in walking for transport Land use mix [48] • Land use mix was positively related to walking for errands • Land use mix was not related to walking to work/school Street connectivity [64] • 500-m buffer: street connectivity was positively related to walking for transport • 1000-m buffer: street connectivity was not related to walking for transport Walkability [25] • Walkability was positively related to the participation in walking for transport • Walkability was not related to the duration of walking for transport [42] • Walkability was positively related to the frequency of walking for transport • Walkability was not related to the duration of walking for transport Bicycle lane [61] • Bicycle lane was not related to cycling for transport • Bicycle network connectivity was positively related to cycling for transport Table 9. Cont.…”
Section: Built Environment Factors Reference Resultsmentioning
confidence: 99%
“…Particularly, access to destinations showed opposite results between walking and cycling for transport. Two studies [56,61] found that access to public transit services was negatively related to cycling for transport. It is possible that people who have easy access to public transport would choose to use it rather than cycling.…”
Section: Comparison Of Results Between Walking and Cycling For Transportmentioning
confidence: 99%
“…From the figure, the zonal demand pattern reveals that a majority of the bicycle attraction flows are from the central business district (CBD) area, while the bicycle production flows are generated from the non-CBD areas. Once the bicycle productions and attractions are estimated from each zone in Figure 3, the primary bicycle O-D matrix is estimated using the doubly constrained gravity model given in Equation (1). Because of the absence of bicycle friction factors from the City of Winnipeg, bicycle trip length introduced by [58] was substituted for the friction factors.…”
Section: Stage 1: Generate a Primary O-d Demandmentioning
confidence: 99%
“…Bicycling is increasing in many urban communities around the world due to the push for sustainable living and other factors [1][2][3]. The volume of bicycle users has increased enough to significantly affect the modal split in such communities.…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed that safety aspects of the roads influence bikers' route choice. Braun et al (2016) investigated how the decision to commute by bicycle was associated with cycling infrastructure, bike share availability, incentive programs and other attributes (e.g., public transport availability). They found that cycling and public transport are competing modes and presence of bicycle lane has a relatively small association with bicycle commuting.…”
Section: Related Workmentioning
confidence: 99%